Assessment of sexual function in Japanese men with prostate cancer undergoing permanent brachytherapy without androgen deprivation therapy: Analysis from the Japanese Prostate Cancer Outcome Study of Permanent Iodine‐125 Seed Implantation database - Okihara, Koji; Yorozu, Atsunori; Saito, Shiro; Tanaka, Nobumichi; Koga, Hirofumi; Higashide, Satoshi; Kikuchi, Takashi; Nakano, Masahiro (International journal of urology, 2017)
Objectives To evaluate male sexual function in Japanese prostate cancer patients undergoing permanent brachytherapy without endocrine treatment, using quality of life measures of the Expanded Prostate Cancer Index Composite. Methods A total of 482 patients were selected as analysis subjects from the nationwide database for the Japanese Prostate Cancer Outcome Study of Permanent Iodine‐125 Seed Implantation. The patients were asked to complete the Expanded Prostate Cancer Index Composite questionnaires before and at 3, 12, 24, and 36 months after the permanent brachytherapy. Changes in their responses were analyzed, and any association of the outcomes was investigated. Furthermore, changes over time in their answers to Q18 (usual quality of your erections) were analyzed. Results A total of 72 patients (14.9%) had received external beam radiation. A total of 68 patients (14.1%) had taken any 5‐phosphodiesterase inhibitor medications. Regarding Q18, 232 patients (48.2%) selected either “There was no sexual activity” or “There was no desire for erection” before receiving permanent brachytherapy. Of all the 482 patients, sexual function was preserved in 138 patients (28.7%) 3 years after permanent brachytherapy. Overall satisfaction has significantly improved without regard for the deterioration of sexual function. Significant factors for maintaining sexual activity were patient age and sexual activity before permanent brachytherapy. Conclusions In Japanese patients undergoing permanent brachytherapy alone for prostate cancer, the sexual function is not well preserved. However, decreased sexual function does not seem to represent a major factor determining patients’ overall satisfaction. These findings might be peculiar to Japanese patients, in whom elderly subjects account for the majority.